Stromatolites as Biosignatures of Atmospheric Oxygenation: Carbonate Biomineralization and UV-C Resilience in a Geitlerinema sp. - Dominated Culture - Popall, Rabja M.; Bolhuis, Henk; Muyzer, Gerard; Sánchez-Román, Mónica (Frontiers in Microbiology, 2020)
Modern stromatolites are key to the record of past microbial activity preserved in fossil carbonate deposits. Mono-phototrophic cultures dominated by the cyanobacterium Geitlerinema sp. were obtained from a laboratory-maintained, low magnesium-calcite stromatolite originating from Lagoa Vermelha, Brazil. This lagoonal system has been described as a Precambrian analogue, illustrating a period of photosynthetically-induced atmospheric oxygenation, which created a global sanctuary from shortwave solar radiation and enabled the evolution of modern life on Earth. The enrichment cultures precipitate carbonates in minimal media, suggesting that cyanobacterial photosynthesis and extracellular polymeric substance production may be crucial in the mineralization of the studied stromatolite. We further show that Geitlerinema sp. can build and maintain filamentous mats under long-term UV-C exposure. Our results suggest that present day stromatolites dominated by cyanobacteria may be interpreted as biosignatures of atmospheric oxygenation and have implications for the search for putative biological traces on Mars.